PENGARUH PENGETAHUAN MANAJER TERHADAP GAYA PENGGUNAAN INFORMASI AKUNTANSI MANAJEMEN DAN ACTIVITY-BASED MANAGEMENT SERTA IMPLIKASINYA PADA PENERAPAN DIAGNOSIS RELATED GROUP - Anastasia Susty Ambarriani (Indonesian Journal of Economics and Business, 2012)
The objective of the research are to find out empirical evidence to investigate the significant impact of manager’s management accounting knowledge on managers’ style in using management accounting information. It then investigated the impact of manager’s style on the existence of activity-based management in those hospitals. Further, this research examines the DRG acceptability among those hospitals effect manager’s knowledge.The population of the research are hospital’s management team. Using stratified simple random sampling method, This research surveyed 68 hospitals in Jogjakarta Special Region and Central Java. This research employed Partial Least Square (PLS) to study the impact of manager’s knowledge on manager’s style in using management accounting information and the impact of this style on the readiness of implementing activity-based management. It also used mann-whitney test for assessing whether the distribution of those variables has equal values in private and public hospitalsThis research found significant impact of managers’ knowledge on manager’s style in using management accounting information and significant impact of this style on the availability of activity based management implementation. This research also found a relatively low acceptability of Diagnosis-Related Group system among surveyed hospitals. This research also found that the relation among those variables are not imply to diagosis-related group implementation. Further, this research found no significant differences in the distribution of those variables between private and public hospitals.The conclusions of the research are; (1)manager’s knowledge in management accounting are not adequate to push hospital’s manager team in using management accounting information in interavtive style; (2) if hospital manager’s management accounting knowledge are good, they would use management accounting information in interactive style. Interactive style in using manafement accounting information system means managers would employ management accounting information system as learning tool for continous improvement within organization, problem solving and formulating strategy that aim to organisation’s misssion and vission achievement; (3) if hospital manager’s use interactive style in using management accounting information, organtation’s would employ activity-based management; (4) Dignosis-related group payment system couldn’t be running well, if there is lack of adequate management accounting information system.